Propriedades da zeólita y contendo mesoporos formados por ação do surfactante CTA+ - Silva, Juliana Floriano da (Universidade Federal de São Carlos, 2018)
Zeolites are microporous, crystalline aluminosilicates that have numerous advantages due to their intrinsic properties such as acidity, hydrothermal stability and shape selectivity. However, the presence of micropores causes diffusion limitations and reduces the accessibility of the molecules to the active sites. To overcome this problem, mesopores are generated in zeolitic framework, combining characteristics of microporous and mesoporous materials. In the present work, the USY zeolite was modified by alkaline treatment in the presence of the CTABr surfactant and subsequently hydrothermal treatment. The influence of the alkaline medium, surfactant concentration, hydrothermal treatment time and temperature on the framework, textural and chemical characteristics of zeolites modified was evaluated. By X-ray diffraction and nitrogen adsorption, it was found that mesopores are generated in the USY zeolite while maintaining its faujasite framework. It has also been observed that the simultaneous presence of the basic medium and the surfactant is required for the formation of mesopores. By dispersive energy spectroscopy (EDS) analysis, it was found that the overall Si/Al ratio of the USY zeolite was kept constant after the modification. The samples were evaluated in the esterification reaction between acetic acid and butanol or tert-butanol, concluding that the amount of acid sites was more relevant than the mesoporosity generated.
Keywords: Zeólitas com mesoporos; Difusão; Esterificação; Zeolites with mesopores; Esterification; Diffusion; ENGENHARIAS::ENGENHARIA QUIMICA